Nutritional Analysis of Aqueous Extract of Snake Fruit Seeds (Salacca Edulis Reinw) for Development of Anemia Treatment - Hani Fara Ayu Febyawati; Dono Indarto; Selfi Handayani (Global Health Science Group, 2023)
Anemia remains a global nutritional problem, which prevalence continues to increase every year. Children, female adolescents, and pregnant women are more susceptible to anemia than other age groups. Prolonged anemia has negative impacts on their life such as premature birth, low birth weight (LBW) babies and intrauterine fetal death. Snake fruit Pondoh (Salacca edulis Reinw) is an original Indonesian fruit, which is well cultivated at the Sleman regency, Yogyakarta. Snake fruit seeds contribute to 25-30% of the total fruit, which has not been established their health effect. Therefore, this study aims to analyze the nutritional content of aqueous extract of snake fruit seeds (AES). The powder of snake fruit seeds was made using a previous method, which was adopted from our research group. The powder was then extracted using hot aqueous with 65°C. A proximate analysis was used to determine the AES nutritional content. A hundred g AES contained 21.92% water, 41.10% carbohydrates, 12.66% protein, 4.51% fat, 0.62% tannins, 32.8 mg Iron, 10.25 mg zinc, 276.42 mg magnesium, and 495.48 mg vitamin C. In conclusion, the AES has complete macronutrients and contains high levels of Iron, Magnesium, and vitamin C, which becomes a potential nutraceutical for anemia treatment. Further research is required to confirm the beneficial effect of AES administration in female rats with anemia.